2018
DOI: 10.1111/aas.13078
|View full text |Cite
|
Sign up to set email alerts
|

Radiologic indicators for prediction of difficult laryngoscopy in patients with cervical spondylosis

Abstract: BackgroundWe identified the most useful variables for prediction of difficult laryngoscopy in patients with cervical spondylosis according to physical indicators and preoperative skeletal X‐ray and soft tissue MRI measurements. We hypothesized that there was a closer association between difficult laryngoscopy and radiologic indicators.MethodsWe randomly enroled 315 patients undergoing elective cervical spine surgery and analysed the radiological and physical data in predicting difficult laryngoscopy.ResultsWe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 27 publications
3
36
0
3
Order By: Relevance
“…Clinically, there are many factors associated with difficulty of intubation during laryngoscopy, including head-neck trauma [ 2 ], airway abnormalities [ 3 ], gastroesophageal reflux disease [ 4 ], hard to open mouth [ 5 ], impaired cervical mobility [ 6 ], etc. The incidence of difficulty to undergo laryngoscopy and intubation ranges widely among different studies, and patients with cervical spondylosis have a higher incidence of difficult laryngoscopy (17.1%) [ 7 ] than those without cervical spondylosis (7.3%) [ 8 ]. This might in turn cause unexpected difficult airways in large proportion of patients, significantly increasing the morbidity and mortality rates [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, there are many factors associated with difficulty of intubation during laryngoscopy, including head-neck trauma [ 2 ], airway abnormalities [ 3 ], gastroesophageal reflux disease [ 4 ], hard to open mouth [ 5 ], impaired cervical mobility [ 6 ], etc. The incidence of difficulty to undergo laryngoscopy and intubation ranges widely among different studies, and patients with cervical spondylosis have a higher incidence of difficult laryngoscopy (17.1%) [ 7 ] than those without cervical spondylosis (7.3%) [ 8 ]. This might in turn cause unexpected difficult airways in large proportion of patients, significantly increasing the morbidity and mortality rates [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In one such study, a large tongue area measured on preoperative computed tomography was associated with difficult laryngoscopy in acromegaly patients [16]. In another study conducted in patients with cervical spondylosis, a long mandibulohyoid distance and large angle of the anterior-inferior point of the upper incisor in the extended neck position were related to difficult laryngoscopy [17]. A short atlanto-occipital distance has also been reported to make laryngoscopy difficult [15].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that body mass index (BMI), Mallampati score, and mouth opening predict difficult intubation with intubation devices such as direct laryngoscopes, videolaryngoscopes, and lightwands [11][12][13][14]. Regarding radiographic indices associated with difficult intubation, tongue area, atlanto-occipital gap, mandibulohyoid distance, and the angle of the anterior-inferior point of the upper incisor with the neck in extension are related to difficult laryngoscopy, while epiglottis length is associated with increased intubation time when using lightwands [15][16][17][18]. Despite the aforementioned advantages of videostylets, no clinical investigation has yet been performed to identify radiographic predictors of difficult intubation with videostylets.…”
Section: Introductionmentioning
confidence: 99%
“…Inappropriate airway management may lead to airway injury, brain hypoxia, and even death. At present, the incidence rate of cervical spondylosis is increasing year by year, and these patients are often confronted with di cult laryngoscopy [2], with the incidence of di cult laryngoscopy to be 17.1% [3], far more than the incidence of 5.8% in the general population [4]. Considering that cervical spondylosis patients are more prone to appear unexpected di cult airway and even emergency airway, such as can't intubation can't ventilation situation, it is fundmentlly important to gure out the most valuable predictor of di cult laryngoscopy in patients with cervical spondylosis.…”
Section: Introductionmentioning
confidence: 99%